IMPLEMENTASI LKPD BERBASIS RADEC SEBAGAI UPAYA PENINGKATAN KEMAMPUAN LITERASI MEMBACA PESERTA DIDIK KELAS V SEKOLAH DASAR - Widodo, Widyawati; Diana, Siska Mega; Profithasari, Nindy; Destini, Frida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low reading literacy skills of fifth-grade students in the Indonesian language subject at SD Negeri 1 Blitarrejo. This study aims to determine the improvement in students’ reading literacy skills. This research uses a quantitative approach. The research design applies a pre-experimental method with a one-group pretest-posttest design. The data collection techniques include reading literacy test items, observation, and documentation. The data are analyzed using the N-Gain test. The results of this study indicate that RADEC-based LKPD has an effect as an effort to improve students’ reading literacy skills in the Indonesian language subject at the elementary school level.